Meningkatkan Pengetahuan Mitigasi Bencana Pada Anak Usia Sekolah Melalui Media Game Edukasi “Utas-Gana” di Desa Pindahan Baru - Eva Alviawati; Karunia Puji Hastuti; Parida Angriani; Akhmad Munaya Rahman; Muhhamad Muhaimin (Borneo Research and Educatin Center, 2021)
This counselling and demonstration were conducted to analyze the improvement of disaster mitigation abilities in school-age children through the educational game media